Electrochemical Detection of Interaction between Verbascum sp. and DNA by Using Disposable Biosensors. (2017) - Subak, H.; Dalar, Abdullah; Ozkan-Ariksoysal, D.
Abstract: Verbascum sp. known as mullein, comprise approximately 250 species of flowering plants, native to Europe and Asia. Multiple species of mullein are commonly used as a plant based nutritional supplement and herbal tea. Infusion and/or decoction prepared from Verbascum cheiranthifolium Boiss. var. cheiranthifolium Boiss. (Scrophulariaceae), known as masicerk, is extensively used to cure rheumatism, menstrual pains and haemorrhoids in Eastern Anatolia. There has still been groving interest in studying DNA-targetted bio(nano)sensors and DNA interactions in recent years. In this study, the electrochemical behavior of the plant extract was monitored and the effect of this extract on DNA was investigated by using biosensor technology. The interaction mechanism of the extract was also examined and evaluated with disposable carbon electrodes by using differential pulse voltammetry (DPV). Thus, the optimal experimental parameters were determined and compared with GC-MS data. The obtained results showed that newly-developed biosensor could be used as a model device for the rapid, cost effective and sensitive detection of plant extract–DNA interaction.